1999
DOI: 10.1038/sj.bjc.6690573
|View full text |Cite
|
Sign up to set email alerts
|

Serum concentrations of vascular endothelial growth factor and nitrite as an estimate of in vivo nitric oxide in patients with gastric cancer

Abstract: SummaryThe importance of tumour angiogenesis in the process of tumour growth and progression in solid tumours has been widely accepted. Among many angiogenic factors, vascular endothelial growth factor (VEGF) has been shown to play a major role in the development and dissemination of the malignant tumours. Nitric oxide (NO) production was also observed in solid tumour tissues. NO has been reported to play an important role for the mitogenic effect of VEGF in the angiogenic process. However, little is known abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 13 publications
1
14
0
Order By: Relevance
“…Elevated plasma concentrations of VEGF have been detected in gastric cancer and are closely related to the extent of the disease [2,5,26]. Compared with the VEGF concentrations in healthy controls (n ϭ 20), VEGF concentrations in 4 patients were elevated, 2 of whom were stage IV patients.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated plasma concentrations of VEGF have been detected in gastric cancer and are closely related to the extent of the disease [2,5,26]. Compared with the VEGF concentrations in healthy controls (n ϭ 20), VEGF concentrations in 4 patients were elevated, 2 of whom were stage IV patients.…”
Section: Discussionmentioning
confidence: 99%
“…By binding to 1 of 3 vegf receptors, vegf results in receptor dimerization, phosphory lation, and downstream stimulation of cell growth and angiogenesis [94][95][96] . Expression of vegf is seen in 42%-49% of gc and has been associated with increased disease burden and worse clinical outcome 92,[97][98][99][100][101][102] . Bevacizumab is a humanized monoclonal antibody against vegfa.…”
Section: Summary Of Evidencementioning
confidence: 99%
“…Higher serum VEGF levels have been associated with increased disease burden [41] and worse clinical outcomes [39,40,[42][43][44] in GC. A prospective biomarker analysis [45] showed that higher levels of VEGF-A are associated with worse survival [46].…”
Section: Vascular Endothelial Growth Factormentioning
confidence: 99%